Recent trends on hydrogel development and sustainable applications: a bibliometric analysis and concise review - Sahu, Kamalakanta; Chakma, Sumedha (Polymer bulletin (Berlin, Germany), 2024)
A bibliometric analysis delves into top-tier research discoveries, providing information that enhances our understanding of diverse research areas. In this context, VOSviewer version 1.6.17 stands out as the preferred choice for visualising Scopus datasets, enabling a more thorough exploration of the subject matter and associated keywords. In our extensive bibliometric investigation spanning from 1992 to 2022, we analysed a total of 12,284 documents associated with the primary keyword ‘hydrogel’, as well as 29 documents related to the secondary keyword ‘hydrogel development’. The bibliometric data revealed a strong presence of hydrogel researchers in China, followed by the USA, South Korea, and Japan. VOSviewer was able to refine the top 2000 documents for the detailed analysis and the most recent articles regarding the parameters such as co-authorship, co-occurrence, citation patterns, and bibliographic coupling. The pursuit for superior and sustainable polymers is essential for modifying the characteristics of hydrogels, boosting their functionality, and maintaining their long-term viability. As a result, selecting sustainable chemicals for hydrogel synthesis becomes a crucial concern in the time being. This review article primarily focuses on comprehending the historical and contemporary processes of hydrogel generation, along with the most recent tools for visualising author networks, keywords, organisational affiliations, and citation patterns. Furthermore, the latter part of this review explores the latest advancements, their accompanying limitations, the significance of these developments, the classification of hydrogels, and their sustainable applications, collectively shedding light on the extensive scope of hydrogels in various domains.